COVID-19 vaccination attitudes and acceptance among people with serious mental illness - Small, William; Silva, Caroline; Johnson, Rachel; Betti, Vincent; Nguyen, Antoinette; Todd, Lauren; Jacobowitz, David; Lamberti, J. Steven (Frontiers in Psychiatry, 2025)
ObjectiveThis study examines attitudes towards COVID-19 vaccination among a diverse cohort of adults with serious mental illness (SMI), participant characteristics that are associated with vaccine acceptance, and barriers to COVID-19 vaccination among this population.MethodsA 28-item questionnaire was administered to 185 adults with SMI receiving care at a university-based outpatient psychiatric clinic. Variables included demographics, health behaviors, and vaccination status. Chi-square tests were used for categorical demographic comparisons on binary COVID-19 vaccine status.ResultsFemale participants were more likely to have received COVID-19 vaccination (77.6%) than male (55.7%) participants. White (73.3%) and Hispanic/Latino (81.8%) participants were more likely to have received vaccination than Black/African American (54.9%) participants. Participants who reported having seen a primary care provider (PCP) within the past two years were more likely to be vaccinated (72.1%) than those who had not (41.7%). Participants who reported having received an influenza vaccine in the past two years were more likely to be vaccinated (80.2%) than those who had not (41.8%). Participants who had not been vaccinated were more likely to report greater concerns about all potential barriers to vaccination, including concerns about side effects, cost, health effects, and distrust of clinicians and governments.ConclusionsThe overall vaccination rate of study participants with SMI was similar to that of the general population. Efforts to enhance engagement in primary care may help improve preventative health behaviors in people with SMI.